ANALISIS GAYA KEPEMIMPINAN ISLAMI DAN BUDAYA KERJA ISLAMI DI RM SINJAY BANGKALAN DALAM PERSPEKTIF EKONOMI SYARIAH - Nanda Shally Maulini; Farid Ardyansyah (Fakultas Ekonomi dan Bisnis Universitas Alma Ata, 2022)
The development of the culinary business is currently getting tighter. Many new competitors have emerged and made culinary businessmen who previously required culinary businessmen to put up a very precise strategy so as not to be outdone by their competitors. Sinjay Restaurant is a restaurant that makes duck the main menu. But even though there are many competitors around it, this Sinjay restaurant is still the most superior. Over time, the development of Sinjay's restaurant is currently growing rapidly. With the rapid progress of the Sinjay restaurant, researchers are interested in the leadership style applied, as well as the work culture used in the Sinjay Bangkalan restaurant. Researchers use descriptive qualitative research types where researchers will conduct research by going directly to the research location. Data collection techniques were carried out in several ways, namely by interviews and documentation. The data obtained by the authors were in the form of primary data and secondary data. after getting the data it will be analyzed first. In conducting data analysis researchers will use descriptive methods. The results of this study indicate that Islamic leadership plays an important role as a guide and reinforcer of Islamic organizational culture to produce optimal organizational performance. The leader of RM Sinjay Bangkalan plays a very important role with this very good work culture, because the leader regulates all aspects implemented by the Sinjay Bangkalan Restaurant. Islamic leadership plays an important role as a guide and reinforcement of Islamic organizational culture to produce optimal organizational performance. The leader of RM Sinjay Bangkalan plays a very important role with this very good work culture, because it is the leader who regulates all aspects implemented by the Sinjay Bangkalan Restauran